DIAGNOSTICS OF THE PROBABILITY OF BANKRUPTCY OF AN AGRICULTURAL SECTOR ENTERPRISE (INNOVATIVE ECONOMY, 2025)
Fedoryshyna L.M., Artemchuk D.V.  DIAGNOSTICS OF THE PROBABILITY OF BANKRUPTCY OF AN AGRICULTURAL SECTOR ENTERPRISEPurpose. The aim of the article is to analysis of the operating environment of agricultural enterprises and determination of the probability of bankruptcy of LLC AE “AHROS-VISTA” with a comparison of the results obtained using different models.Methodology of research. The following general and special research methods were used to achieve the set goal, in particular: analysis, monographic, abstract and logical, systematization ‒ to study the problems of agricultural enterprises and their characteristics, and to evaluate the performance indicators of enterprises; Lees and Taffler models ‒ to determine the probability of bankruptcy of LLC AE “AHROS-VISTA” in 2022‒2023; tabular ‒ for a visual presentation of the initial data and calculations performed.Findings. Key problems of the functioning of agricultural enterprises were identified, including external risks associated with military operations; volatility of world and domestic markets; financial and credit constraints; technological and innovation challenges; personnel problems; climate and natural risks; uneven regional development; regulatory and institutional risks. The performance indicators of enterprises under СTЕA A01 (Classification of types of economic activity A01) Crop and animal production, hunting and related service activities for 2020-2024 were analysed. The probability of bankruptcy of LLC AE “AHROS-VISTA” was diagnosed using the Lis and Taffler models based on data from 2022‒2023 and it was found that it is not threatened with bankruptcy, since the calculated values significantly exceed the limit values. Originality. The study of the operating environment of agricultural enterprises with the identification of key challenges, as well as determination of the probability of bankruptcy of an agricultural enterprise, has received further development.Practical value. The results of the study can become the basis for further scientific research in the context of improving existing/searching for new models for predicting the probability of bankruptcy of agricultural enterprises, taking into account its specifics (dependence on weather conditions, uneven cash flows, volatility of the world agricultural market, etc.).Key words: agricultural sector, enterprise, bankruptcy, Lis model, Taffler model, diagnostics, risk, probability of bankruptcy.
Keywords: agricultural sector; enterprise; bankruptcy; Lis model; diagnostics; Taffler model; risk; probability of bankruptcy